2022
DOI: 10.1097/jom.0000000000002563
|View full text |Cite
|
Sign up to set email alerts
|

Disparity in Occupational Health Risk During the Pandemic

Abstract: Objective: This study clarifies potential misestimation of occupational risk caused by the dichotomy of frontline essential and nonessential occupations in prior studies. Methods: The linear regression is used to investigate the occupational risk in terms of incidence rate, hospitalization, and mortality on community level during the pandemic. Results: Overall, frontline essential occupations were positively associated with incidence rate, hospitalization, and mortality (156.06, 18.47, and 3.49; P < 0.01). Amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
(98 reference statements)
0
2
0
Order By: Relevance
“…We used the Baker 39 assignment as a proxy for telework, but it is possible that workers in certain occupations assigned to one of the three “work outside the home” quadrants actually worked from home during the pandemic and that occupations assigned to the “work from home” reference group (Q1) worked outside the home. For instance, the relatively low rate in Q2 might in part reflect the fact that this quadrant included workers in many health care and education occupations who may have had the ability to work from home during 2020, and were therefore at lower risk of work‐related SARS‐CoV‐2 exposure 33,50,54,56 . In their study, Yuan et al 56 found that, overall, working in frontline essential occupations was positively associated with COVID‐19 incidence, hospitalization and mortality, but closer examination of occupation groups revealed a negative association among education, training and library occupations (essential), which in our analysis were largely included in Q2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the Baker 39 assignment as a proxy for telework, but it is possible that workers in certain occupations assigned to one of the three “work outside the home” quadrants actually worked from home during the pandemic and that occupations assigned to the “work from home” reference group (Q1) worked outside the home. For instance, the relatively low rate in Q2 might in part reflect the fact that this quadrant included workers in many health care and education occupations who may have had the ability to work from home during 2020, and were therefore at lower risk of work‐related SARS‐CoV‐2 exposure 33,50,54,56 . In their study, Yuan et al 56 found that, overall, working in frontline essential occupations was positively associated with COVID‐19 incidence, hospitalization and mortality, but closer examination of occupation groups revealed a negative association among education, training and library occupations (essential), which in our analysis were largely included in Q2.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the relatively low rate in Q2 might in part reflect the fact that this quadrant included workers in many health care and education occupations who may have had the ability to work from home during 2020, and were therefore at lower risk of work‐related SARS‐CoV‐2 exposure 33,50,54,56 . In their study, Yuan et al 56 found that, overall, working in frontline essential occupations was positively associated with COVID‐19 incidence, hospitalization and mortality, but closer examination of occupation groups revealed a negative association among education, training and library occupations (essential), which in our analysis were largely included in Q2. The authors speculated that online teaching technology might have allowed for remote learning, thereby reducing the risk of occupational exposure for workers in education.…”
Section: Discussionmentioning
confidence: 99%